Influence of Probenecid on the Pharmacokinetics and Pharmacodynamics of Sorafenib - Koen G. A. M. Hussaarts; Leni van Doorn; Karel Eechoute; Jeffrey Damman; Qiang Fu; Nadia van Doorn; Eric D. Eisenmann; Alice A. Gibson; Esther Oomen-de Hoop; Peter de Bruijn; Sharyn D. Baker; Stijn L. W. Koolen; et al. (Pharmaceutics, 2020)
Prior studies have demonstrated an organic anion transporter 6 (OAT6)-mediated accumulation of sorafenib in keratinocytes. The OAT6 inhibitor probenecid decreases sorafenib uptake in skin and might, therefore, decrease sorafenib-induced cutaneous adverse events. Here, the influence of probenecid on sorafenib pharmacokinetics and toxicity was investigated. Pharmacokinetic sampling was performed in 16 patients on steady-state sorafenib treatment at days 1 and 15 of the study. Patients received sorafenib (200–800 mg daily) in combination with probenecid (500 mg two times daily (b.i.d.)) on days 2–15. This study was designed to determine bioequivalence with geometric mean Area under the curve from zero to twelve hours (AUC0–12 h) as primary endpoint. During concomitant probenecid, sorafenib plasma AUC0–12 h decreased by 27% (90% CI: −38% to −14%; P < 0.01). Furthermore, peak and trough levels of sorafenib, as well as sorafenib concentrations in skin, decreased to a similar extent in the presence of probenecid. The metabolic ratio of sorafenib-glucuronide to parent drug increased (+29%) in the presence of probenecid. A decrease in systemic sorafenib concentrations during probenecid administration seems to have influenced cutaneous concentrations. Since sorafenib-glucuronide concentrations increased compared with sorafenib and sorafenib-N-oxide, probenecid may have interrupted enterohepatic circulation of sorafenib by inhibition of the organic anion transporting polypeptides 1B1 (OATP1B1). Sorafenib treatment with probenecid is, therefore, not bioequivalent to sorafenib monotherapy. A clear effect of probenecid on sorafenib toxicity could not be identified in this study.